Design and Preclinical Development of TransCon PTH, an Investigational Sustained‐Release PTH Replacement Therapy for Hypoparathyroidism. (9th October 2019) - Holten‐Andersen, Lars; Pihl, Susanne; Rasmussen, Caroline E; Zettler, Joachim; Maitro, Guillaume; Baron, Julia; Heinig, Stefan; Hoffmann, Eric; Wegge, Thomas; Krusch, Mathias; Faltinger, Frank; Killian, Steffen; et al.
ABSTRACT: Hypoparathyroidism (HP) is a condition of parathyroid hormone (PTH) deficiency leading to abnormal calcium and phosphate metabolism. The mainstay of therapy consists of vitamin D and calcium supplements, as well as adjunct Natpara (PTH(1‐84)). However, neither therapy optimally controls urinary calcium (uCa) or significantly reduces the incidence of hypercalcemia and hypocalcemia. TransCon PTH, a sustained‐release prodrug of PTH(1‐34) in development for the treatment of HP, was designed to overcome these limitations. To determine the pharmacokinetics and pharmacodynamics of TransCon PTH, single and repeat s.c. dose studies were performed in rats and monkeys. TransCon PTH demonstrated a half‐life of 28 and 34 hours in rats and monkeys, respectively. After repeated dosing, an infusion‐like profile of the released PTH, characterized by low peak‐to‐trough levels, was obtained in both species. In intact rats and monkeys, daily subcutaneous administration of TransCon PTH was associated with increases in serum calcium (sCa) levels and decreases in serum phosphate levels (sP). In monkeys, at a single dose of TransCon PTH that increased sCa levels within the normal range, a concurrent decrease in uCa excretion was observed. In 4‐week repeat‐dose studies in intact rats and monkeys, uCa excretion was comparable to controls across all dose levels despite increases in sCa levels. Further, in a rat model of HP, TransCon PTH normalized sCa and sP levels 24 hours per day. This was in contrast to only transient trends toward normalization of sCa and sP levels with an up to 6‐fold higher molar dose of PTH(1‐84). After repeated dosing to HP rats, uCa excretion transiently increased, corresponding to increases in sCa above normal range, but at the end of the treatment period, uCa excretion was generally comparable to sham controls. TransCon PTH was well tolerated and the observed pharmacokinetics and pharmacodynamics were in line with the expected action of physiological replacement of PTH. © 2019 American Society for Bone and Mineral Research.